Antioxidant Properties of Bioactive Compounds in Fruit and Vegetable Waste - Nerea Jiménez-Moreno; Irene Esparza; Carmen Ancín-Azpilicueta (MDPI AG, 2023)
In recent years, great interest has arisen in the study of compounds with antioxidant activity present in agri-food residues [...]